2013
DOI: 10.1016/j.ygeno.2013.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing and microarray-based interrogation of microRNAs from formalin-fixed, paraffin-embedded tissue: Preliminary assessment of cross-platform concordance

Abstract: Next-generation sequencing is increasingly employed in biomedical investigations. Strong concordance between microarray and mRNA-seq levels has been reported in high quality specimens but information is lacking on formalin-fixed, paraffin-embedded (FFPE) tissues, and particularly for microRNA (miRNA) analysis. We conducted a preliminary examination of the concordance between miRNA-seq and cDNA-mediated annealing, selection, extension, and ligation (DASL) miRNA assays. Quantitative agreement between platforms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…2 copies of miR-203 could be detected by sequencing; 4) the levels of U6 snRNA and miR-211, miR-451a, let-7i, miR-203 and miR-205 were readily amplified and measured using qRT-PCR in 101 archived specimens and 5) having obtained 1,351,417 sequences representing 698 distinct mature known miRNAs. These findings in conjunction with other recent studies [46], [47] establish that miRNA deep sequencing on FFPE cancer tissues is feasible and RNA degradation to the degree observed dose not affect miRNA profiling.…”
Section: Discussionsupporting
confidence: 84%
“…2 copies of miR-203 could be detected by sequencing; 4) the levels of U6 snRNA and miR-211, miR-451a, let-7i, miR-203 and miR-205 were readily amplified and measured using qRT-PCR in 101 archived specimens and 5) having obtained 1,351,417 sequences representing 698 distinct mature known miRNAs. These findings in conjunction with other recent studies [46], [47] establish that miRNA deep sequencing on FFPE cancer tissues is feasible and RNA degradation to the degree observed dose not affect miRNA profiling.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have indicated that RT-qPCR can be performed to quantify miRNA expression using archival FFPE tissue samples (46,47). The present study employed FFPE tissue samples from lung cancer and normal tissues to identify miRNAs deregulated in patients with lung cancer: miRNA-21-5p was upregulated and miR-623, -30e-5p and -363-3p were downregulated in lung cancer samples compared with control pulmonary bulla specimens.…”
Section: A B C Dmentioning
confidence: 94%
“…By examining assay repeatability on decreasing amounts of FFPE RNA, we demonstrated that 100 ng of FFPE RNA were sufficient for sequencing miRNAs from archived specimens. We also found that our modified procedure was highly reproducible ( r > 0.96) when using specimens up to 35 years old, further suggesting that archived specimens subjected to extended storage contain well-preserved miRNAs that can be purified, cloned and sequenced [12,19,20,21,22,29,33]. Our repeated measures performed at different time intervals further display that this laboratory-based optimized protocol should be applicable to large-scale FFPE-RNA studies, which require successive weeks of experimentation.…”
Section: Discussionmentioning
confidence: 96%
“…We evaluated the performance of our modified approach using gold standard matched fresh/frozen and FFPE human tissues/cells and demonstrated that FFPE RNA provides high quality miRNA expression data relative to its matched fresh/frozen counterpart, when using NGS [19,20,21,22,33]. By examining assay repeatability on decreasing amounts of FFPE RNA, we demonstrated that 100 ng of FFPE RNA were sufficient for sequencing miRNAs from archived specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation